Ответы и объяснения

2014-02-16T07:36:55+00:00
1)  2(а-1) +32а-2+3 = 2а-1
       а-1             а-1       а-1
2) х^2- х(х-а) = х^2- x^2+ xa=    xa
   х^2 - a^2      x^2-a^2           x^2- a^2  
3) a(a+b)- ab = a^2+ab- ab = a^2
     a+b                a+b           a+b
Лучший Ответ!
2014-02-16T07:44:17+00:00
1) =(2(a-1))/(a(a-1) ) +3a/(a(a-1))
2) =x^2 /  ((x-a)(x+a))-x(x+a) /((x-a)(x+a))
3) =a(a+b)/(a+b) -ab/(a+b)
4) =((x-2y)^2) * (x+2y)) /((x-2y)(x+2y)) +(x+2y)^2  *  (x-2y)) /((x+2y)(x-2y))
5) =7/((x-y) x+y)) +5/(x(x-y))- 12/(x(x+y))=7x/(x(x-y)(x+y)) +(5(x+y))/(x((x-y)(x+y)) -(12(x-y))/(x(((x-y)(x+y))